Microclimate impact of harvester trails in Picea abies continuous cover stands in boreal Sweden - Vigren, Carl (2017)
This study aimed to compare the microclimate 20 cm above the ground in the harvester trail to the inner sections of selectively felled Norway Spruce (Picea abies (L.) H. Karst) stands in the Jämtland province in boreal Sweden. Data was provided by Klara Joelsson, who had placed the iButtons © hydrocrone 1923 instrument in the plots, which took readings of the relative humidity and temperature every 2 hours between the 6th of June and 19th of October 2015. The general linear model showed that sites in the harvest trail experienced a temperature span increase (24,70%) as the daily maximum temperature increased (12%) and the daily minimum temperature decreased (-4,8%) to new extremes compared with the inner stand. Maximum daily relative humidity is rather unaffected (+0,85%), but Minimum relative humidity decreased (-7,1%). A light index was calculated from fish-eye images with Gap Light Analyzer, in which the ratio of incoming (direct and diffuse) solar radiation just above the ground is compared to the amount above the canopy. With this could be shown that for every percent the ratio increased, the maximum daily temperature increased by 0,08 C°; the minimum temperature decreased by 0,02 C°); the temperature span recorded during the day increased by 0,10 C° and the daily minimum humidity decreased by 0,24 %rh. The daily maximum temperature and temperature span is greatly influenced by the amount of transmitted light from the canopy, indicating that there may be a great deal of in-stand variation dependent upon smaller gaps.